Lack of sense of life and suicide: In which circumstances medical paternalism may be justified? - Espínola-Nadurille, Mariana; Sánchez-Barroso, José Antonio; Páez-Moreno, Ricardo; Sánchez-Guzmán, María Alejandra; Ramírez-Bermúdez, Jesús (Acta Bioethica, 2014)
Aims: Description of a clinical case addressed by using a bioethical focus. Materials and methods: Relevant facts were clarified and moral problems were identified by moral deliberation; main ethical problem was selected and courses of action were suggested. Results and conclusions: In this clinical case the most prudent solution was justified paternalism. The practice of moral deliberation is essential since decisions frequently surpass medical techniques and demand the deliberation of moral values.